Nuclear Fusion Research Understanding Plasma-Surface Interactions - Clark, Robert E. H.; Reiter, Detlev; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
It became clear in the early days of fusion research that the effects of the containment vessel (erosion of "impurities") degrade the overall fusion plasma performance. Progress in controlled nuclear fusion research over the last decade has led to magnetically confined plasmas that, in turn, are sufficiently powerful to damage the vessel structures over its lifetime. This book reviews current understanding and concepts to deal with this remaining critical design issue for fusion reactors. It reviews both progress and open questions, largely in terms of available and sought-after plasma-surface interaction data and atomic/molecular data related to these "plasma edge" issues.
Atomic and Surface Data Issues in Nuclear Fusion -- Plasma—Wall Interaction: Status and Data Needs -- Modeling of Fusion Edge Plasmas: Atomic and Molecular Data Issues -- Energy Deposition from ELMs in Fusion Devices -- Plasma Diagnostics -- Molecular Diagnostics of Cold Edge Plasmas -- Divertor Spectroscopy with Molecular Transport -- High-Temperature Plasma Edge Diagnostics -- X-ray Spectroscopy of High n Transitions of He- and Ne-Like Ions in Alcator C-Mod Plasmas -- High-Temperature Plasmas Diagnostics by X-ray Spectroscopy in the Low Density Limit -- Surface Processes and Material Issues -- Review and Status of Physical Sputtering and Chemical Erosion of Plasma Facing Materials -- Hydrogen Retention in and Release from Carbon Materials -- Interaction of Low-Energy Ions and Hydrocarbon Radicals with Carbon Surfaces -- Tritium Inventory in the Materials of the ITER Plasma-Facing Components -- Mixed and High-Z Plasma-Facing Materials in TEXTOR -- Beryllium and Liquid Metals as Plasma Facing Materials -- Databases -- IAEA Databases and Database Establishment Programs -- NIFS DATABASE and Cooperation with IAEA DCN -- The NIST Atomic Structure Databases -- The Atomic Data and Analysis Structure -- Collision Processes of Atomic and Molecular Hydrogen in Fusion Plasmas: The Cross-Section Data Status -- Partial and Differential Electron Impact Ionization Cross-Sections for Small Hydrocarbon Molecules.
Keywords: Nuclear fusion; Nuclear energy; Atoms; Physics; Plasma (Ionized gases).; Materials—Surfaces.; Thin films; Nuclear Fusion; Nuclear Energy; Atoms and Molecules in Strong Fields, Laser Matter Interaction; Plasma Physics; Surfaces and Interfaces, Thin Films